A gendered analysis of the effect of financial inclusion on household welfare in Burundi - Atta-Aidoo, J.; Matthew, E.C.; Saleh, A.O.; Bizoza, S. (Wiley, 2025)
Despite an improving financial inclusion situation across the developing world, there still exist wide gender gaps in financial inclusion, especially in fragile and post-conflict countries. In our study, we designed and implemented a survey consisting of 860 households across urban and rural Burundi to examine the effect of financial inclusion on household asset-based welfare from a gendered perspective. To address any endogeneity concerns, we apply the two-stage least squares (2SLS) regression method. We find that most Burundian households prefer to save their money at home rather than at a financial institution. Also, mobile money is mainly employed as a means of receiving and withdrawing cash. Our 2SLS regression results reveal that improved financial inclusion has a greater effect on the welfare of female-headed households than on male-headed households. We recommend the use of social networks as an avenue to promote financial inclusion and literacy. Additionally, the Government of Burundi can collaborate with the telecommunication operators to institute small loan schemes through the mobile money platform to enhance access to credit, especially for women.